Assessing the bird and tree species diversity in the north of Badung, Bali, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Yuni LPEK, Wijaya IMS, Sari IAEP. 2022. Assessing the bird and tree species diversity in the north of Badung, Bali, Indonesia. Biodiversitas 23: 4482-4489. Bird diversity is related to tree diversity, which is influenced by landscape heterogeneity. Here, we reported the bird diversity of Jempanang, Bali, Indonesia, in riparian, plantation, and forest edge habitats estimated through a point count survey undertaken in June 2021, and related to patterns of tree diversity. Overall, Jempanang had a high diversity of bird and tree species, with 54 bird species and 18 tree species recorded in total. Among habitats, bird diversity was highest in the riparian area, whereas the plantation and forest edges had moderate bird diversity. The plantation had the lowest absolute tree diversity, but all sites had a moderate level of tree diversity. The wide range of land uses in Jempanang provides a diverse composition of plant species, thereby increasing the number of environmental niches and driving higher diversity of bird species. The presence of apex raptor species indicates that Jempanang can be considered an area with good environmental quality. Considering the high diversity of bird and tree species in the area, birdwatching activities could be promoted as an agent for community-based conservation, potentially providing local incentives for preserving the area’s biodiversity.
Keywords: Bird, diversity, point count, tree, vegetation analysis